Volatilitiy of World Food Commodity Prices and Renewable Fuel Standard Policy - Farida, Ida; Singagerda, Faurani Santi (International Journal of Energy Economics and Policy, 2020)
Biofuel as an alternative fuel which in recent years has become the world's demand for renewable energy fuels and is a major factor underlying the increase in prices of agricultural commodities, especially corn as the main commodity for biofuels in the US. The purpose of this study is to examine the volatility of several world food commodities, namely rice, wheat, corn, and soybeans and to analyze the impact of biofuel development on the price volatility of some world food commodities. This research uses coefficient of variation and volatility analysis with the ARCH GARCH method. Based on the results, the price of food commodities is more volatile after the adoption of the Renewable Fuel Standard 2 (RFS) policy in 2007. The results of the study show that development of biofuels (from corn and soybeans) have a higher level of volatility than the other two commodities (rice and wheat) due to the variance of rice and wheat was lower than corn and soybeans. It means that the greater the relevance of a commodity to the development of biofuels, the higher the price volatility of the commodity. Meanwhile, the expansion of biofuels also made US reduce the amount corn and soybean exports, of course this is what makes the supply of US corn and soybeans decreased and makes the price will increase. Keywords: renewable energy, volatility, Renewable Fuel Standard (RFS) policy, commodity prices JEL Classifications: L5, O13, O21, O44, P18 DOI: https://doi.org/10.32479/ijeep.10037